OLESAN MINYAK ZAITUN MENGURANGI DERAJAT RUAM POPOK PADA ANAK 0-24 BULAN - Wanodya Hapsari; Fajaria Nur Aini (Jurnal Sains Kebidanan, 2019)
This study was to determine the reduction in the degree of diaper rash with olive oil spread. Problems that are often found onthe baby's skin are diaper rash and are associated with external irritants such as dirt, material from diapers, urine, microorganisms, and friction caused by diapers and recur. The incidence of diaper rash in Indonesia reaches 7-35% which afflicts boys and girls under three years old. Non-pharmacological therapy in diaper rash, which is to eliminate or reduce skin moisture and friction by replacing diapers according to capacity, applying olive oil that contains antioxidants in high amounts of vitamin E (α-tocopherol) and phenolic compounds.The design of this study was quasi-experimental, with a sample of 22 infants divided into 2 groups, each with 11 diapers rashes smeared with olive oil and 11 other infants using only cloth diapers that were changed every time they were wet, finished chapter and tub. The population in this study were children aged 0-24 months who experienced diaper rash. The sampling technique in this study uses a non-probability sampling method with a purposive sampling technique. Analysis with Wilcoxon statistical tests.The results of the study showed a significant difference between the spread of olive oil and the use of cloth diapers on the degree of diaper rash with a significant number of 0.007 at p 0.05.